Analisis Efektivitas Rule Snort dalam Mendeteksi Serangan Jaringan - Suci Sekar Sari; Agus Tedyyana (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
The effectiveness of snort rules in detecting network attacks is still a question that needs further research. Although snort rules have been developed and updated regularly, network attacks also continue to evolve and may have patterns that have not been detected by existing snort rules. The main objective is to develop and analyze the effectiveness of snort rules in detecting attack patterns on the network. Benefits Provides a better understanding of the effectiveness of snort rules in detecting network attacks. The result of this research is that the development of snort rules that have been carried out is able to filter attack patterns that were previously undetectable such as DDoS attacks and is able to provide telegram notifications.